Orchesting Inclusive Evaluation in Schools. Where We Could Start? - Mª Amparo Calatayud (Universidad Autónoma de Madrid, 2019)
It is true that in recent years a lot of progress has been made in a discourse of powerful and informed inclusivity, but the practices follow the inertia of an evaluation that starts from the fact that all students are equal. It continues to drag an evaluative culture based on the fact that learning is at the service of evaluation and teaching ends up subordinated to the latter. A deep-rooted reductionist and qualifying culture, resistant to change and that costs a lot to rebuild and transform towards an assessment for inclusion. In theory, we have gone from an evaluation focused on the verification of knowledge, certification, control, qualification, etc. and in which all students are equal to a consideration of the evaluation as an opportunity for learning and in which each student is unique and different. That is why, in this article we try to articulate the genuine nautical charts towards real inclusiveness in the educational centers, subsequently influencing in one of those letters, the one related to the inclusive evaluation to end with the presentation of some of the strategies that can make this assessment a reality in inclusive classrooms